2020
DOI: 10.34117/bjdv6n7-248
|View full text |Cite
|
Sign up to set email alerts
|

Atributos de crescimento e concentração de micronutrientes em mudas de maracujazeiros irrigadas com águas salinas e uso de UOV

Abstract: Atributos de crescimento e concentração de micronutrientes em mudas de maracujazeiros irrigadas com águas salinas e uso de UOV Growth attributes and micronutrient concentration in passion fruit seedlings irrigated with saline water and UOV use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
0
0
1
Order By: Relevance
“…These results may be related to the synergism between zinc and nitrogen in their processes of absorption (Cessa et al, 2017). Results similar to those of the present study were found by Nascimento & Freire (2020), who observed higher accumulation of zinc in yellow passion fruit seedlings.…”
Section: /7supporting
confidence: 92%
See 1 more Smart Citation
“…These results may be related to the synergism between zinc and nitrogen in their processes of absorption (Cessa et al, 2017). Results similar to those of the present study were found by Nascimento & Freire (2020), who observed higher accumulation of zinc in yellow passion fruit seedlings.…”
Section: /7supporting
confidence: 92%
“…The present study corroborates the information provided by Nascimento & Freire (2020) according to which iron was one of the most accumulated micronutrients in the leaf tissue of yellow passion fruit. Contrary to the present study, Lima et al (2009) describe that substrates with CB did not have a positive effect on the Fe element in soursop seedlings.…”
Section: /7supporting
confidence: 92%
“…O segundo método tem como principal vantagem que não há necessidade de retirar as folhas, preservando-se a sua integridade. Diversas pesquisas têm sido realizadas com a finalidade de estimar a área foliar de culturas agrícolas e árvores perenes por meio de equações e modelos alométricos (MALDANER et al, 2009;FIGUEIREDO et al, 2010;SILVA et al, 2011;MORGADO et al, 2013;ZEIST et al, 2014;MATOS et al, 2015;FONSECA et al, 2020;NASCIMENTO e FREIRE, 2020;PEREIRA et al, 2020;ALMEIDA JÚNIOR et al, 2021). Contudo, a partir desses estudos infere-se que os coeficientes e o tipo de modelo dependem das condições climáticas do local, classe de solo e variedade da cultura.…”
Section: Introductionunclassified